The ECG of high-level junior soccer players: comparing the ESC vs the Seattle criteria - Bessem, B.; de Bruijn, M. C.; Nieuwland, W. (British Journal of Sports Medicine, 2015)
Introduction: Sudden cardiac death in young athletes is a devastating event. The screening and detection of potentially life-threatening cardiac pathology by ECG is difficult due to high numbers of false-positive results, especially in the very young. The Seattle ECG criteria (2013) were introduced to decrease false-positive results. We compared the Seattle ECG criteria with the European Society of Cardiology (ESC) ECG criteria of 2005 and 2010 for cardiac screening in high-level junior soccer players.Methods During the 2012-2013 season, all data from cardiovascular screenings performed on the youth division of two professional soccer clubs were collected. The total study population consisted of 193 male adolescent professional soccer players, aged 10-19 years. Five players dropped out of this study.Results Applying the ESC criteria of 2005 and 2010 to our population resulted in a total of 89 (47%) and 62 (33%) abnormal ECGs. When the Seattle ECG criteria were applied, the number of abnormal ECGs was 6 (3%). The reduction was mainly due to a reclassification of the long QT cut-off value and the exclusion of right atrial enlargement criteria. All ECG abnormalities using the Seattle criteria related to T-wave inversion criteria.Conclusion The Seattle ECG criteria seem very promising for decreasing false-positive screening results for high-level junior soccer players.